Performance analysis of single-phase interior permanent magnet synchronous motor - Benjamin Olabisi Akinloye; Emeka Simon Obe (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Single-phase permanent magnet synchronous motor has been tipped as an alternative to single-phase induction motor due to its high efficiency and torque density. Consequently, a proper performance analysis of the motor is required to cope with the stator imbalance in order to prevent pulsation in the torque performance. This paper presented the dynamic and steady-state analysis of a single-phase interior permanent magnet synchronous motor. In this analysis, a proper combination of direct-quadrature (d-q) reference frame, and symmetrical component analyses were used. The symmetrical components analysis was used to obtain the steady state performance while the dynamic performance was obtained from d-q analysis. The symmetrical components cope with the imbalance and hence the resulting torque pulsation which may results in heating of the motor. The results obtained agreed with the theoretical analysis and yielded a unique steady state equivalent circuit and phasor diagram. The models of the motor were simulated using MATLAB/Simulink. A prototype of the motor was developed and experimentation was carried out to validate the dynamic performance.